Kerentanan Perempuan dalam KBGO: Studi Kasus Perlindungan Hukum bagi Korban KBGO oleh Kolektif Advokat Untuk Keadilan Gender - Pramidazzura Alifa Rifqi; Hartiwiningsih Hartiwiningsih; Riska Andi Fitriono (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Technological advancements have increased the forms and types of crimes, including online gender-based violence (GBV). The COVID-19 pandemic has driven Indonesian society to engage in online activities, leading to a 23% increase in internet usage by April 2020, but also triggering a surge in cyberattacks, with 190 million cases recorded during the same period. Cases of online GBV have risen from 281 in 2020 to 1697 in 2023. This research examines the vulnerability of women to online GBV and the challenges faced by the Gender Justice Advocates Collective (KAKG) in providing legal protection. Factors such as patriarchal culture, lack of digital literacy, objectification of women, and victim-blaming culture exacerbate women's vulnerability. KAKG faces obstacles including limited human resources, insufficient family support, and difficulties in determining the location of crimes. This study employs a non-doctrinal method, examining the implementation of laws in society. Interview data indicate that the majority of online GBV victims are women, with a significant increase in complaints from 2022 to 2023. The study highlights the importance of digital literacy education and training for law enforcement officers with a victim-centered and gender-equitable perspective to effectively handle online GBV cases.